MINAT SISWA TERHADAP MATEMATIKA DENGAN METODE PEMBELAJARAN DAN EFIKASI DIRI - Suyatno, Sugeng (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aimed to describe students' interest in mathematics with learning methode and selfefficacy. The population of this research were junior high school students in Pulau Rimau This is aquantitative descriptive research, studied 653 students which were selected using the stratified random samplingtechnique. Data in this study consisted of data on student?s interest in mathematics (Y), learning methode (X1),and student?s self-efficacy (X2) which were obtained using questionnaires. Data analized using correlation andmultiple linear regression with ? = 0.05. It were concluded that: (i) 22.58% of students have interests in highcategory, 76.56% with moderate category, and 0.86% in low category; (ii) there is a very strong positiverelationship between the variables of learning method and self-efficacy together towards the variables of interestwith a value of r = 0.844; (iii) there is a strong positive relationship between learning method and interest inmathematics when no change of self-efficacy with r = 0.505; (iv) there is a strong relationship between selfefficacy and interest in mathematics when the learning method does not change with r = 0.585; and (v) theformula of the linear regression model is Y = 22,788+0,972 X1+0,932 X2.